Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/infdis/jiaa618
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Neutralizing Antibody Titers in the Months After Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: Most individuals infected with SARS-CoV-2 develop neutralizing antibodies that target the viral spike protein. Here we quantify how levels of these antibodies change in the months following SARS-CoV-2 infection by examining longitudinal samples collected between ~30 and 152 days post symptom onset from a prospective cohort of 32 recovered individuals with asymptomatic, mild, or moderate-severe disease. Neutralizing antibody titers declined an average of about four-fold from one to four months post symptom onse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
195
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(241 citation statements)
references
References 41 publications
37
195
2
Order By: Relevance
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref. 12 ) and 5/80 (ref.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref. 12 ) and 5/80 (ref.…”
Section: Discussionsupporting
confidence: 90%
“…In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref. 12 ) and 5/80 (ref. 31 ) individuals with a decline to undetectable neutralizing antibodies (ID 50 < 20 or ID 50 < 50, respectively) at the last timepoint studied.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…positive patients had statistically significant higher antibody levels against most antigens compared to not ventilated COVID-19 positive patients. This confirms similar findings that individuals with more severe disease have higher antibody levels (9,10,11,12,13,14). Further studies need to be done to understand the relationship between increased antibody production and ventilation.…”
Section: Correlation Of Igg Antibody Levels and Il-10supporting
confidence: 87%
“…Neutralizing antibodies to SARS-CoV-2 develop in most individuals after infection but decay with time 7,8,[27][28][29][30][31] . These antibodies are effective in prevention and therapy in animal models and are likely to play a role in protection from re-infection in humans 32 .…”
Section: Extended Data Fig 8b-k and Supplementarymentioning
confidence: 99%